THE INFLUENCE OF STEAM-BASED PROJECT-BASED LEARNING MODELS ON STUDENTS' LEARNING OUTCOMES IN CLASS IV ENERGY TRANSFORMATION MATERIAL AT MIN 6 BIREUEN - Putri Susiana (Faculty of Tarbiyah nad Teacher Training, 2023)
The importance of choosing a learning model. A good learning model can be used to make the teaching and learning process more effective, meaningful and enjoyable. So that students will get learning outcomes that can meet the minimum completeness criteria (KKM). But the fact is that teaching and learning in class is still not optimal in using learning models. Based on these problems need an update. One of the meaningful, effective, and fun learning alternatives that can be applied in developing student competencies is to use the STEAM-based project based learning model. The formulation of the problem in this study is